2020
DOI: 10.25046/aj050138
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Manufactured Sand (M-Sand) as Partially and Fully Replacement of Fine Aggregate in Concrete

Abstract: This, research work was to study the potential of M-sand as compared to river sand in concrete, here M-sand is replaced by river sand 0%,45%,50%,55% and 100% in the concrete mix, Mix design is designed as per IS Standards. In this research a mix 1:2.32:2.82 (M20) was considered. The test specimen was casted for 7days, 28 days and 90days. The performance of M-sand was determined by several experiments such as slump test, impact strength test, flexural Strength, and compressive strength test. The results attaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…The results concur with [4] in a study on the effect of manufactured sand as a replacement for fine aggregates in Concrete who found that the values reveal a gradual increase of the strength when the 0.00 The implication from the study findings that 25% replacement of MMS with river sand increases the compressive strength of concrete. Hence, partially replacements are recommended in construction activities.…”
Section: Figure 3: Compressive Strength At Various Percentage Replace...supporting
confidence: 90%
See 2 more Smart Citations
“…The results concur with [4] in a study on the effect of manufactured sand as a replacement for fine aggregates in Concrete who found that the values reveal a gradual increase of the strength when the 0.00 The implication from the study findings that 25% replacement of MMS with river sand increases the compressive strength of concrete. Hence, partially replacements are recommended in construction activities.…”
Section: Figure 3: Compressive Strength At Various Percentage Replace...supporting
confidence: 90%
“…As a study conducted by [4] in India determined the impact of manufactured sand as partially and fully replacement of fine aggregate in concrete. The results showed that, manufactured sand properties are similar to river sand, M-sand is slightly coarser as compared to river sand.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation